Cerebral venous sinus thrombosis due to oral contraceptive use: Postmortem 3 T-MRI and autopsy findings - Masahiro Uemura; Yoshihiro Tsukamoto; Yasuhisa Akaiwa; Masaki Watanabe; Ayako Tazawa; Sou Kasahara; Minoru Endou; Ryosuke Ogura; Kouichirou Okamoto; Yukihiko Fujii; Tsutomu Nakada; Akiyoshi Kakita; et al. (Elsevier, 2016)
Cerebral venous sinus thrombosis (CVST) is an uncommon form of stroke, and mortality of the acute phase is high. We report the clinical, postmortem 3 T-MRI, and autopsy features of a patient, 20-year-old Japanese woman, with CVST who died shortly after starting to use low-dose estrogen combined hormonal contraceptives (CHCs). A postmortem 3 T-MRI study with our originally developed system revealed abnormal intensities suggestive of thrombi extending throughout the straight sinus and left sigmoid sinus. At autopsy, in accordance with the images, we performed careful preparations of the sinuses. Histological examination revealed an organizing white thrombus occupying the lumen of the left sigmoid sinus, and an acute, red thrombus in the lumen of the left transverse, straight, and tentorial sinuses, and vein of Galen, indicating that the thrombus had developed first in the left sigmoid sinus, then extended retrogradely to the more proximal portion of the sinus system, reaching the vein of Galen. The features of the present CVST patient appear to be informative, when encountering CHC users with neurological symptoms, even in those who begun to use low-dose estrogen CHCs only recently.